Identification and Investigation of Ethnobotany of Some Medicinal Plants in Razavi Khorasan Province - M Hosseini; M Rahim Forouzeh; H Barani (Institue of Medicinal Plants, ACECR, 2019)
Introduction: Ethnobutany, as a part of every region's national capital, contains local beliefs and knowledge about plants and their characteristics being the result of centuries of trial and error in the natural environment. Though, it is unwritten and exposed to degeneration. Purpose: The purpose of this study was to acquire and document the culture of traditional use of Zebarkhan rangeland medicinal plants from Neyshabur in Razavi Khorasan province. Method: In this study, the traditional knowledge of the people about the plants was collected in free interviewing and participatory observations. Questions posed about local names, growth form, harvest methods, organ usages and properties of plants. Interviews then went on until the repeated responses confirmed the reliability and validity. Collected Plants were identified by applying valid botanic sources. Result: The existence of 70 medicinal plants in Neyshabur rangelands confirms the richness of this region, so identification and documentation of their indigenous knowledge can pave the way for a better usage of medicinal plants and their products. Conclusion: In this study, 70 medicinal plant species belonging to 29 families were identified. The largest proportion of plant species were respectively related to Lamiaceae, Apiaceae, Brassicaceae and Polygonaceae. Among traditional uses, the most belonged to diseases treatment related to digestive, colds, neurological problems and sedation. The most commonly used organs were floral branches, leaves and young stems. Investigating and comparing different uses of plants in the study area as well as the other parts of Iran proves the similarity usage of similar plant species in different regions of the country.